Determining the Best Advertising Medium for a Footwear Company : A Case Study - Majeed, Rabeeb Abdul; Sriram, K. V. (Indian Journal of Marketing, 2019)
Decision makers at times find it difficult to make a rational decision when many criteria and sub-criteria are to be considered while choosing an alternative. The purpose of this study was to find a solution for such a situation in a footwear company, which was confronted with a dilemma in determining the best advertising medium. The project incorporated multi - criteria decision - making (MCDM) methodology ; in specific, it used the analytical hierarchy process (AHP) along with the hierarchical structural model approach. It considered five criteria and four sub-criteria obtained from previous research studies. The application of the technique was successful in finding the best advertising medium. Visual media was found to be the best advertising media, followed by print media, closely followed by social media, and corporate social responsibility (CSR) activities. The study provides the decision makers in confining their choices to four alternatives namely visual media, social media, print media, and CSR. The study was set to help the marketing managers in the future if they were faced with a situation to choose the best alternative based on several criteria. The study presented insights into the importance of advertising for a footwear company, importance of selecting an efficient media for advertising, and the implementation of CSR as a marketing strategy for a footwear company.